Using the PDCA methodology for automating the badge printing process through Low-Code Tools - Sardinha, Leonardo Lopes; Fonseca Júnior, Lázaro Antônio da; Santos, Aline Gonçalves dos (Brazilian Journal of Production Engineering, 2024)
This article addresses the automation of the employee badge printing process in a company using low-code programming tools. The problem was structured according to the Lean methodology, specifically the PDCA cycle. Gemba Walk and 5W2H were used to list the identified issues, which ranged from delays in badge delivery, lack of control over the number of badges printed, time wasted due to duplicate photos and decentralized information, as well as the manual creation of badges. With the implementation of the low-code solution, these problems were effectively resolved. The automated system not only optimized the workflow and minimized manual errors but also enabled the verification of expired training and examinations. Additionally, the solution resulted in approximately an 84% reduction in the time required for badge request and printing.